2004
DOI: 10.1159/000076118
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy with Synthetic Opioids and Driving Aptitude

Abstract: Aims: To assess the influence of methadone and buprenorphine maintenance treatment on the driving aptitude of opioid-dependent patients. Design: Prospective, open label, outpatient maintenance, single-blind (investigator) study. Participants and Setting: Thirty opioid-dependent patients maintained on either methadone or buprenorphine were recruited from the drug-addiction outpatient clinic in Vienna. Measurements: The traffic-relevant performance dimensions of the participants were assessed 22 h after receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 25 publications
2
14
0
2
Order By: Relevance
“…Any restrictions on their right to drive, if such are necessary, should have a scientific basis. As Schindler et al [38] have stated in their publication, 'the safe operation of a motor vehicle is a learned activity demanding the complex interaction of physical, cognitive, perceptual, and psychological skills and abilities', the results of this study indicate that these skills are not diminished in patients receiving opioid maintenance therapy. However, there is a clear need for more information on road safety and driving capability in these patients.…”
Section: Discussionsupporting
confidence: 52%
“…Any restrictions on their right to drive, if such are necessary, should have a scientific basis. As Schindler et al [38] have stated in their publication, 'the safe operation of a motor vehicle is a learned activity demanding the complex interaction of physical, cognitive, perceptual, and psychological skills and abilities', the results of this study indicate that these skills are not diminished in patients receiving opioid maintenance therapy. However, there is a clear need for more information on road safety and driving capability in these patients.…”
Section: Discussionsupporting
confidence: 52%
“…The effects of OAT on patient´s driving ability are controversial (Baewert et al, 2007;Fishbain et al, 2003;Loeber et al, 2012;Schindler et al, 2004). Although OAT might impair driving ability, it does so to a less degree than other psychotropic agents or drugs of abuse (Soyka, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Only 7 studies dealt with the performance among BMPs compared to various control groups (Baewert et al 2007;Lenne et al 2003;Messinis et al 2009;Pirastu et al 2006;Rapeli et al 2007;Schindler et al 2004;Soyka et al 2008), where 6 studies found impairment. The total number of tests revealing impairment was 22 out of a total of 83 (n = 15-22, daily doses ranging from 6.78 to 15.8 mg/day).…”
Section: Methadonementioning
confidence: 99%